'How Can You Just Cut Off a Whole Side of the Family and Say Move On?' The Reshaping of Paternal Grandparent-Grandchild Relationships Following Relationship Breakdown in the Middle Generation - O'DWYER, CIARA MARY; DOYLE, MARTHA; TIMONEN, VIRPI (My University, 2010)
Based on a qualitative study of 31 grandparents, this article highlights how separation in the middle generation can result in an erosion of trust and quality of paternal grandparent-grandchild relationships. Despite these changes, grandparents endeavour to support and remain involved in the lives of their grandchildren by inter alia compensating for a perceived lack of their sons? parenting skills, affirming their grandchild?s position in the paternal kin network and acting as a mediator between the separated couple to ensure continued contact with grandchildren. The findings suggest that the actions of paternal grandparents can potentially have important future implications not only for the grandparent-grandchild relationship, but also the relationship trajectories of their adult son and child in the post-separation family.
PUBLISHED
Keywords: Divorce; grandchildren; grandparents; intergenerational relationships; separation; critical role transitions